Friction factors of power-law fluids in chevron-type plate heat exchangers - Fernandes, Carla S. (2008)
In the present work laminar flows of Newtonian and power-law fluids through cross-corrugated chevron-type plate heat exchangers (PHEs) are numerically studied in terms of the geometry of the channels. The plates area enlargement factor was a typical one (1.17), the corrugation angle, β, varied between 30° and 60° and the flow index behaviour, n, between 0.25 and 1. Single friction curves fReg = K for both Newtonian and non-Newtonian fluids are proposed for each β by developing an adequate definition of the generalised Reynolds number, Reg. The coefficient K compares well with experimental data, for all (seven) values of β, and depends on the tortuosity coefficient, τ. It was found that, for each β, τ decreases with the decrease of n. Food fluids are frequently processed in PHEs and usually behave as non-Newtonian fluids. This study can be useful in engineering applications as well as in the characterization of transport phenomena in PHEs.